Full-field acoustomammography using an acousto-optic sensor - Sandhu, J. S. (American Association of Physicists in Medicine, 2009)
In this Letter the authors introduce a wide-field transmission ultrasound approach to breast imaging based on the use of a large area acousto-optic (AO) sensor. Accompanied by a suitable acoustic source, such a detector could be mounted on a traditional mammography system and provide a mammographylike ultrasound projection image of the compressed breast in registration with the x-ray mammogram. The authors call the approach acoustography. The hope is that this additional information could improve the sensitivity and specificity of screening mammography. The AO sensor converts ultrasound directly into a visual image by virtue of the acousto-optic effect of the liquid crystal layer contained in the AO sensor. The image is captured with a digital video camera for processing, analysis, and storage. In this Letter, the authors perform a geometrical resolution analysis and also present images of a multimodality breast phantom imaged with both mammography and acoustography to demonstrate the feasibility of the approach. The geometric resolution analysis suggests that the technique could readily detect tumors of diameter of 3 mm using 8.5 MHz ultrasound, with smaller tumors detectable with higher frequency ultrasound, though depth penetration might then become a limiting factor. The preliminary phantom images show high contrast and compare favorably to digital mammograms of the same phantom. The authors have introduced and established, through phantom imaging, the feasibility of a full-field transmission ultrasound detector for breast imaging based on the use of a large area AO sensor. Of course variations in attenuation of connective, glandular, and fatty tissues will lead to images with more cluttered anatomical background than those of the phantom imaged here. Acoustic coupling to the mammographically compressed breast, particularly at the margins, will also have to be addressed.